2017
DOI: 10.1370/afm.2136
|View full text |Cite
|
Sign up to set email alerts
|

Continuity of Primary Care and Emergency Hospital Admissions Among Older Patients in England

Abstract: PURPOSE Secondary health care services have been under considerable pressure in England as attendance rates increase, resulting in longer waiting times and greater demands on staff. This study's aim was to examine the association between continuity of care and risk of emergency hospital admission among older adults. METHODSWe analyzed records from 10,000 patients aged 65 years and older in 2012 within 297 English general practices obtained from the Clinical Practice Research Datalink and linked with Hospital E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 38 publications
4
42
0
Order By: Relevance
“…Previous research on this topic consistently found it to have unfavorable effects on patient‐centered outcomes . A pioneering randomized controlled trial in older veterans found discontinuity to be associated with decreased patient satisfaction and increased hospitalizations, and observational studies corroborated these findings for the broader population (albeit limited by reverse causality bias) and found associations with adverse drug events, myocardial infarction, and increased mortality in generalist and specialist practices . Our review suggests that physician retirement is associated with similar negative consequences.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Previous research on this topic consistently found it to have unfavorable effects on patient‐centered outcomes . A pioneering randomized controlled trial in older veterans found discontinuity to be associated with decreased patient satisfaction and increased hospitalizations, and observational studies corroborated these findings for the broader population (albeit limited by reverse causality bias) and found associations with adverse drug events, myocardial infarction, and increased mortality in generalist and specialist practices . Our review suggests that physician retirement is associated with similar negative consequences.…”
Section: Discussionsupporting
confidence: 66%
“…Previous research on this topic consistently found it to have unfavorable effects on patient-centered outcomes. 28,29 A pioneering randomized controlled trial in older veterans found discontinuity to be associated with decreased patient satisfaction and increased hospitalizations, 30 and observational studies corroborated these findings for the broader population 29,[31][32][33] (albeit limited by reverse causality bias) 34 and found associations with adverse drug events, myocardial infarction, and increased mortality in generalist and specialist 24 Reliable: methods were clearly described Sampling bias: sampled population were ED users, excluded patients with higher acuity and those unable to complete survey Cross-sectional design: primary aim was to determine the proportion of ED users with connection to a family doctor, does not allow us to infer causality Markussen et al 25 Reliable: methods were clearly described Valid: primary aim was to determine whether physicians influence workplace absence among their patients; used national administrative data and several analytic methods to identify retirement, match controls, and adjust for seasonal and patient-specific variance in outcome Sampling bias: studied only patients who were working employees No reporting of ethics approval Limited applicability: only two outcomes chosen (variance in sick pay claims and subsequent patient-initiated switches in primary care physician)…”
Section: Discussionmentioning
confidence: 97%
“…The value associated with a 14% reduction in costs is roughly $1,000/beneficiary/year. Higher continuity, measured at the patient level using BB-COC, was recently shown to be significantly associated with reduction in emergency care for elderly patients in England, 21 and a recent systematic review found significant, positive association between continuity and reduced mortality. 22 Continuity is already endorsed by the National Quality Forum as a quality measure for children with complex care needs, and these findings suggest that continuity may be useful as a physician-level measure for quality and/ or resource use under the QPP.…”
Section: Discussionmentioning
confidence: 99%
“…See Supplemental Table 2 for regression results (Supplemental Table 2 Regression Coef cient in people identifying a usual source of care. 21,24 There is a strong, national effort to move Medicare providers into value-based payment, including the federal QPP, and the alignment of such payment with high-value primary care functions would logically be a priority. Our research has limitations, and further work is needed to understand how continuity measurement might impact provider behavior.…”
Section: Discussionmentioning
confidence: 99%
“…8 The repeated touches enabled by continuity of care appear to be an antidote to emergency hospital admissions, in a study of records from 10,000 patients. 9 The argument for causation is strengthened by the observed dose-response pattern. Balint's notion of doctor as drug 10 finds support in this study.…”
mentioning
confidence: 99%